2016
DOI: 10.1021/acsami.6b12240
|View full text |Cite
|
Sign up to set email alerts
|

Superacidity in Nafion/MOF Hybrid Membranes Retains Water at Low Humidity to Enhance Proton Conduction for Fuel Cells

Abstract: A hybrid membrane of superacid sulfated Zr-MOF (SZM) and Nafion shows much superior performance to Nafion, particularly for fuel cell operating under low humidity. The Brønsted acidic sites in SZM networks retain an ample amount of water which facilitated proton conduction under low humidity. The water retention properties of Nafion-SZM hybrid membranes with 1 wt % loading of SZM increased at 35% relative humidity and outperformed commercial unfilled Nafion membrane. The proton conductivity increases by 23% fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
103
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(110 citation statements)
references
References 34 publications
4
103
0
Order By: Relevance
“…However, their proton conduction channels are not consecutive enough and the fabrication of MOFs into the form of membranes is still immature, which restricts their proton conductivity and limits their practical application. The fabrication of MOFs into sulfonated polymer matrix is a significant step for their practical application (Patel et al, 2016;Dong et al, 2017). Sulfonated polymers are not only easy-to-prepare membranes, but also act as a good medium to form continuous and effective channels for proton conduction.…”
Section: Introductionmentioning
confidence: 99%
“…However, their proton conduction channels are not consecutive enough and the fabrication of MOFs into the form of membranes is still immature, which restricts their proton conductivity and limits their practical application. The fabrication of MOFs into sulfonated polymer matrix is a significant step for their practical application (Patel et al, 2016;Dong et al, 2017). Sulfonated polymers are not only easy-to-prepare membranes, but also act as a good medium to form continuous and effective channels for proton conduction.…”
Section: Introductionmentioning
confidence: 99%
“…Patel and coworkers studied the effect of sulfated Zr‐MOF‐808 (SZM) on Nafion membranes. The Nafion/SZM hybrid exhibited 23% increased ionic conductivity over the unfilled Nafion membranes at 35% relative humidity (RH) . Wu's group reported the effect of co‐doping of two different MOF (UiO‐66‐NH 2 and UiO‐66‐SO 3 H) in Nafion membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The Nafion/SZM hybrid exhibited 23% increased ionic conductivity over the unfilled Nafion membranes at 35% relative humidity (RH). 29 Wu's group reported the effect of co-doping of two different MOF (UiO-66-NH 2 and UiO-66-SO 3 H) in Nafion membranes. They found that the co-doping of the two different MOFs in Nafion caused more continuous hydration channels that greatly enhanced the proton conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Various membranes have been prepared incorporating filler material e.g. metal organic framework, graphene, silica nanoparticles etc for enhancing membrane performance . In recent year many researchers are focusing on carbon nanotubes due to its impressive optical, electrical, thermal and mechanical properties that make them amenable to a range of applications including water purification, catalysis, hydrogen storage, fuel cell etc .…”
Section: Introductionmentioning
confidence: 99%
“…metal organic framework, graphene, silica nanoparticles etc for enhancing membrane performance. [12][13][14][15][16] In recent year many researchers are focusing on carbon nanotubes due to its impressive optical, electrical, thermal and mechanical properties that make them amenable to a range of applications including water purification, catalysis, hydrogen storage, fuel cell etc. [17][18][19][20] Membranes based on CNTs have remarkable properties such as high flux, high selectivity and low fouling which makes them useful for NF process.…”
Section: Introductionmentioning
confidence: 99%